Safety and immunogenicity of a candidate parvovirus B19 vaccine - Bernstein, David I.; Sahly, Hana M. El; Keitel, Wendy A.; Wolff, Mark; Simone, Gina; Segawa, Claire; Wong, Susan; Shelly, Daniel; Young, Neal S.; Dempsey, Walla (Vaccine, 2011)
Parvovirus B19 is an important human pathogen causing erythema infectiosum, transient aplastic crisis in individuals with underlying hemolytic disorders and hydropsfetalis. We therefore evaluated a parvovirus B19 virus like particle (VLP) vaccine. The safety and immunogenicity of a 25μg dose of parvovirus B19 recombinant capsid; 2.5 and 25μg doses of the recombinant capsid given with MF59; and saline placebo were assessed in healthy adults. Because of 3 unexplained cutaneous events the study was halted after enrollment of 43 subjects and before any subject received their third scheduled dose. The rashes developed 5–9 days after the first or second injection and were seen in one placebo recipient (without an injection site lesion) and two vaccine recipients (with injection site reactions). No clear cause was established. Other safety evaluations revealed mostly injection site reactions that were mild to moderate with an increase in pain in subjects receiving vaccine and MF59. After dose 2 the majority of vaccine recipients developed ELISA and neutralizing antibody to parvovirus B19. Given the possible severe consequences of parvovirus B19 infection, further development of a safe and effective vaccine continues to be important.